PENGUATAN LITERASI EKONOMI KOMUNITAS MELALUI KOPERASI LOKAL PADA MASYARAKAT KALITAN KOTA SURAKARTA - Yahya, Alvin; Nurohman, Yulfan Arif; Kusuma, Melia; Astuti, Yuni (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
Low levels of financial literacy are a problem in managing business finances and utilizing cooperatives to promote economic independence in urban communities. This community service program aims to improve economic literacy and financial behavior in the Kalitan community, Surakarta City, through a structured, participatory training model involving local cooperatives as strategic partners. The program is divided into three main stages: case study-based economic literacy training, business financial management simulations, and technical guidance on using cooperative services. This program significantly improved participants' understanding of financial planning, economic decision-making, and the role of cooperatives in supporting micro-enterprises. Furthermore, this activity also encouraged changes in financial behavior toward more rationality and strengthened trust in community financial institutions. This program serves as an effective model for inclusive economic learning, particularly in urban areas with existing limitations. The program's results demonstrate the important role of cooperatives as agents of community-based economic education and empowerment. The program's novelty combines an experiential learning approach with institutional strengthening of cooperatives within a grassroots economic empowerment framework, a concept rarely explored in Indonesian community service literature